On the determinability of free trioids by semigroups of endomorphisms - Zhuchok, Yu.V. (Reports of the National Academy of Sciences of Ukraine, 2015)
We prove that the endomorphism semigroups of two free trioids are isomorphic if and only if the corresponding free trioids are isomorphic.